The Effect of Basic Life Support (BHD) Training on The Skills of Grade XII Students of The Non-Nursing Program at Nusantara Vocational High School (SMK) Palu - Warihan Unok; Raden Bagus Edy Santoso; Sirli Agustiani; Lili Rahmawati; Fadly Umar; Windu Unggun Cahya Jalu Putra (Promotif : Jurnal Kesehatan Masyarakat, 2026)
Introduction: Basic Life Support (BLS), or Bantuan Hidup Dasar (BHD), is an essential emergency response skill that can be performed by trained laypersons before professional medical assistance arrives. Students may become first responders in school or community settings; therefore, practical BHD training is needed to improve their emergency response skills. This study aimed to determine the effect of BHD training on the skills of grade XII non-nursing students at SMK Nusantara Palu. Methods: This study used a pre-experimental design with a one-group pre-test and post-test approach. A total of 39 grade XII non-nursing students were selected using purposive sampling. The intervention consisted of structured BHD training using explanation, demonstration, guided practice, and simulation with a cardiopulmonary resuscitation manikin. Students’ BHD skills were assessed before and after training using an observation checklist. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test. Results: Before training, most students were in the poor skill category (59.0%). After training, the proportion of students in the good skill category increased to 66.7%, while the poor category decreased to 2.6%. The median BHD skill score increased from 52.00 before training to 84.00 after training. The Wilcoxon Signed Rank Test showed a significant difference in BHD skills before and after training (Z = -5.432; p = 0.000). Conclusion: BHD training significantly improved the practical skills of grade XII non-nursing students at SMK Nusantara Palu. Structured BHD training should be considered as a routine school-based emergency preparedness program.